Penerapan Teknologi Pengolahan Es Mangrove Boba (MaBo) Melalui Kemitraan Perguruan Tinggi dan Kelompok Masyarakat di Pulau Maitara Kota Tidore Kepulauan - Salim Abubakar; Rina; Riyadi Subur; Imalita Tahir; Ariyati H. Fadel; Sunarti; Yuyun Abubakar; M. Abjan Fabanjo; M. Said Al Hadad; Darmiyati Muksin; Faizal Rumagia; Najamuddin; M. Janib Achmad; Raut Wahyuning Paluphi; Sahlan Norau; Iwan Hi Kader; Nebuchadnezzar Akbar; Rizki M. Nur (Universitas Mataram, 2026)
Bruguiera gymnorrhiza fruit has considerable potential as an alternative food resource with nutritional and economic value; however, its utilization by local communities on Maitara Island remains limited. This Community Partnership Program (PKM) aimed to implement the processing technology of Mangrove Boba Drink (MaBo) through a partnership between a higher education institution and a community group to diversify mangrove-based food products and strengthen the local creative economy. The program was conducted in Maitara Utara Village, Tidore Islands City, Indonesia, using a participatory approach involving community outreach, training on raw material selection, mangrove flour processing, boba production, preparation of three MaBo variants (MaBo Neutral, MaBo Full, and MaBo Local), sensory evaluation, and technical assistance for the Marirasa Creative Group. The results showed that all participants successfully mastered the MaBo processing technology and produced products that were well accepted by the sensory panel, with all attributes receiving scores within the